An atoms first approach to general chemistry laboratory - Dieckmann, Gregg R.; Sibert, John W. (New York : McGraw-Hill, 2012)
This laboratory manual presents a lab curriculum that is organized around an atoms-first approach to general chemistry.
Keywords: Chemistry -- Laboratory manuals